Strategi Komunikasi Tenant Relations dalam Meningkatkan Hubungan Baik dengan Tenant di Mall Epiwalk - Fachrianda, Maulana; Syarief, Fauzi (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This study aims to analyze the tenant relations communication strategy implemented by Epiwalk Mall in maintaining and improving good relations with tenants. Effective communication plays an important role in building trust, increasing satisfaction, and loyalty of tenants towards mall managers. This study uses a descriptive qualitative method with a case study approach through observation, interviews, and documentation analysis. The communication techniques applied include face-to-face communication, use of digital media, surveys, and a responsive and proactive personal approach. This strategy allows managers to understand tenant needs, handle complaints quickly, and create mutually beneficial relationships. The results of the study indicate that the combination of these communication techniques not only increases tenant satisfaction but also strengthens Epiwalk Mall's image as a professional and caring business partner. The collaborative and empathetic approach applied in interactions with tenants creates a comfortable and productive work environment. This study provides theoretical contributions to the field of tenant relations communication and offers practical recommendations for mall managers in improving relations with tenants for business sustainability.